Urinary Biomarkers of Oxidative Stress in Aging: Implications for Prediction of Accelerated Biological Age in Prospective Cohort Studies. (6th May 2022) - Mukli, Peter; Wu, Dee H.; Csipo, Tamas; Owens, Cameron D.; Lipecz, Agnes; Racz, Frigyes Samuel; Zouein, Fouad A.; Tabak, Adam; Csiszar, Anna; Ungvari, Zoltan; Tsitouras, Panayiotis D.; Yabluchanskiy, Andriy
Abstract : Background . Aging is a major risk factor for a range of chronic diseases. Oxidative stress theory of aging has been previously proposed as one of the mechanisms responsible for the age-related decline in organ/tissue function and the development of age-related diseases. Urine contains rich biological information on the health status of every major organ system and can be an important noninvasive source for biomarkers of systemic oxidative stress in aging. Aims . The objective of this cross-sectional study was to validate a novel panel of urinary oxidative stress biomarkers. Methods . Nucleic acid oxidation adducts and oxidative damage markers of lipids and proteins were assessed in urine samples from nondiabetic and currently nonsmoking subjects (n = 198 ) across different ages (20 to 89 years old). Urinary parameters and chronological age were correlated then the biological age of enrolled individuals was determined from the urinary oxidative stress markers using the algorithm of Klemera and Doubal. Results . Our findings showed that 8-oxo-7, 8-deoxyguanosine (8-oxoG), 8-oxo-7, 8-dihydroguanosine (8-OHdG), and dityrosine (DTyr) positively correlated with chronological age, while the level of an F2 -isoprostane (iPF2 α -VI) correlated negatively with age. We found that 8-oxoG, DTyr, and iPF2 α -VI were significantly higher among accelerated agers compared to nonaccelerated agers and that a decision tree model could successfully identify accelerated agers with an accuracy of >92%. Discussion . Our results indicate that 8-oxoG and iPF2 α -VI levels in the urine reveal biological aging. Conclusion . Assessing urinary biomarkers of oxidative stress may be an important approach for the evaluation of biological age by identifying individuals at accelerated risk for the development of age-related diseases.